Career potential assessment for elementary students: Exploring intelligence, interests, and personality traits - Zamralita Zamralita; Debora Basaria; Reza Fahlevi; Philomena Esti Widyastuti (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
Improving the quality of education in Indonesia requires paying early attention to students' potential, particularly recognizing their talents, interests, and personality traits. The Community Service Team aimed to provide sixth-grade students at Students of SDN X in West Java with psychological assessments to gain a comprehensive understanding of their intelligence, interests, and personalities. The activity was conducted in collaboration with the Faculty of Psychology at Universitas Tarumanagara and the community service team. This research uses three methods: (1) Socialization and coordination; (2) Assessment; and (3) Collecting data and analyzing quantitatively. Fifty students participated in the assessment, which used the CPM, SDS Holland, and ENS_48 measurement tools. The results indicated that 76 percent of the students had a high level of intelligence. The most dominant interest areas were artistic (21%), enterprising (21%), investigative (20%), and social (17%). The most prominent personality traits were agreeableness (34 percent), extraversion (24%), and conscientiousness (20%). These results offer valuable insights to teachers and parents for designing learning strategies that cater to students' potential.